TYPE AND GROUP POLYSACCHARIDES OF GROUP D STREPTOCOCCI - Elliott, S. D. (The Rockefeller University Press, 1960)
Polysaccharides extracted from cell walls of 4 serological types of Group D streptococci were serologically type-specific. Acid hydrolysates of all 4 contained hexosamine (glucosamine), rhamnose and glucose. A polysaccharide extracted from 2 serological types by either alkaline treatment or mechanical disruption was serologically group-specific. Acid hydrolysates contained glucose and no other single component in comparable amount. The group-specific polysaccharide, which may be of a dextran-like nature, is probably situated wholly or in part at the surface of the streptococcus.